Akayét Um Marup = Hikayat Um Marup = Epopée Um Marup - Po Dharma; Weber, Nicolas; Abdullah Zakaria Bin Ghazali (Koleksi manuskrip Melayu Campa = Collection des manuscrits cam, 2007)
Cham classical literature and manuscript.